تدابير إدارة أزمة كوفيد 91 وتداعياتها على التعليم الابتدائي - - 9199 دراسة حالة ابتدائية ''موس ى بريش" 91 - باي., رانيا; بوليف, صبرينة (University of Eloued جامعة الوادي, 2023)
ترتب عن التدابير التي أتخذتها الحكومة الجزائرية لمواجهة أزمة كوفيد 19، عدة آثار ونتائج على سيرورة العملية التعليمية الأمر الذي أحدث تغيُّرا في مستوى التحصيل العلمي لدى تلاميذ المستوى الابتدائي، ولهذا هدفت هذه الدراسة البحثية لمعرفة مدى نجاعة السياسات التي انتهجها صناع القرار في الجزائر لإدارة أزمة كورونا (كوفيد 19) في تسيير المؤسسات التعليمية الخاصة بالمرحلة الابتدائية، وقد توصلت الدراسة إلى أن إدراة أزمة كوفيد 19 لم تكن بأساليب علمية مسبقة وإنما كانت مجرد حلول استعجالية علاجية لجأت إليها الدولة الجزائرية لمكافحة هذا الوباء.The measures taken by the Algerian government to confront the Covid 19 crisis resulted in several effects and results on the course of the educational process, which caused a change in the level of educational attainment among primary level students, and for this reason this research study aimed to find out the extent of the effectiveness of the policies adopted by decision makers in Algeria to manage the Corona crisis. (Covid 19) in the management of educational institutions for the primary stage, and the study concluded that the management of the Covid 19 crisis was not by prior scientific methods, but rather it was merely an urgent therapeutic solution that the Algerian state resorted to to combat this epidemic.
Measures to manage the COVID-19 and its impacts on primary education Case study of Bribeche Moussa school (2019 - 2022)
مذكرة ماستر
Keywords: تدابير، أزمة كوفيد19، التعليم الابتدائي.; Measures, COVID-19 crisis, primary education.